Research of properties on graphite conductive slag in asphalt concrete - Sun Jian (E3S Web of Conferences, 2020)
Conductive asphalt concrete can eliminate snow and icing on road areas, and is a research hot topic for intelligent snow removal. By adding graphite, the electrical resistivity of asphalt concrete can be reduced to achieve the purpose of electrical conductivity. However, the aggregate electrical resistance in asphalt concrete is very large and does not play a conductive role. It is a new technical idea to use steel slag with good electrical conductivity as aggregate to mix graphite powder with good electrical conductivity to prepare steel slag graphite conductive asphalt concrete (SGCAC). In this paper, the effects of steel slag and graphite on the conductive properties of steel slag graphite conductive asphalt concrete are separately explained, and then the conductive mechanism and electrical resistance stability of the conductive slag and graphite are studied.